Numerical simulation of the churning losses in vehicle rear axle hypoid gear. (August 2019) - Huang, Fengyun; Liu, Weiteng; Zou, Lin; Xu, Jinli
Abstract: A simplified 3D flow field numerical model of rear axle including passive bevel gear and the differential housing is established, based on the VOF (Volume of Fluid) model and the RNG k-ε turbulence model. With the model, the transient oil flow distribution and the influence law of speed, viccosity and bolt structure on the velocity field and the power losses is obtained. In general, the churning power losses increases with the rotational speed and viscosity while the rotational speed has more impact than viscosity on the power losses. The fluid region and the flow velocity increases with the rotational speed and the bolt structure causes a high speed area with the larger velocity gradient in the backflow surface of the bolts, implying the bolts can generate additional churning torque.